Clinical assessment of deleterious oral habits and dental caries–periodontal parameters among Turkish twins - Sabiha Ceren İlisulu; Sinem Birant; Yelda Kasimoglu; Mine Koruyucu; Elif Bahar Tuna İnce; Figen Seymen (Journal of Dental Sciences, 2023)
Abstract Background/purpose: Twin studies are crucial to assess the relative contribution of genetic and environmental factors. This study was conducted to evaluate association between deleterious oral habits and dental caries–periodontal parameters among Turkish twins. Materials and methods: The study comprised 143 pairs of dizygotic (DZ) twins and 59 pairs of monozygotic (MZ) twins aged 3–15 years. Twins were examined for dental caries, plaque index, gingival index, bleeding on probing and deleterious oral habits. Mann Whitney U test was used to examine the data. Results: The MZ twin pairs consisted of 60 male and 58 female twin pairs, whereas the DZ twin pairs consisted of 144 male and 142 female. The mean age of the twins was 9.63 ± 3.0 in MZ twins and 9.47 ± 3.2 in DZ twins. The mean DMFS value of MZ twins with bruxism is higher than those of MZ twins without bruxism (P = 0.001). The mean DMFS value of DZ twins with pacifier sucking is lower than those without (P = 0.007). A statistically significant difference was found between MZ twins with and without nail biting in terms of bleeding on probing and dmfs values (P = 0.035; P = 0.012). The mean values of the plaque index increased due to the mouth breathing in DZ twins (P = 0.024). Regarding the bleeding on probing, there was a statistically significant difference between MZ twins with and without atypical swallowing (P = 0.016). Conclusion: These findings suggest that dental caries–periodontal parameters are similarly affected by deleterious oral habits in MZ and DZ twins.